Introduction to sport law - Spengler, John O. 1962- (John Otto); Baker, Thomas A.; Connaughton, Daniel 1963-; Anderson, Paul M. (Paul Martin) 1969- (Champaign, IL Human Kinetics, 2016)
Introduction to Sport Law With Case Studies in Sport Law, Second Edition, provides students with comprehensive information on the fundamental legal issues in sport and sport management using a jargon-free approach that is accessible to readers with little or no legal background. The content covers legal and management matters most commonly found in sport management, including liability issues, protecting the legal rights of athletes and employees, and managing legal risk. These texts contain straightforward examples and case studies that deliver timely information to ground sport law theory in practical applications. Fully updated and expanded, Introduction to Sport Law, Second Edition, helps students understand the types of law that are most relevant to sport management professionals. New references and updated court cases throughout the text allow students to see laws and issues from a contemporary point of view to further their comprehension. A new chapter on labor law adds a current perspective for students and sport management professionals. Introduction to Sport Law, Second Edition, is organized in a progressive way that takes into account all law categories relevant to sport management. The text presents an overview of the United States legal system, including the court system, the various types of law, and legal resources. It then explores important topics, including labor law, risk management, employment law, gender equity, intellectual property, agency law, tort law, constitutional law, antitrust law, and contract law. Each chapter provides students with unique insight on the law at hand, examining its relevance from the perspective of both sport management and law professionals, and provides an understanding of its real-world application. Objectives and a glossary of terms to assist students with comprehension and knowledge retention are included in each chapter, and many examples are used to assist in grounding the theory. In the Courtroom sidebars present discussion questions, comprehension checks, and applied perspectives, while Moot Court Cases give students an opportunity to debate hypothetical scenarios and apply principles that they have recently learned to conceptualize the technicalities of sport law. Introduction to Sport Law With Cases Studies in Sport Law, Second Edition, presents a comprehensive examination of legal issues in sport. Through its focus on legal concepts with direct application to the sport manager's role and a presentation devoid of legalese, this text provides readers with the information they need in order to feel confident with the fundamentals of sport law.
Chapter 1. U.S. Legal System ; Sources of U.S. Law ; U.S. Court System ; Types of U.S. Law ; Legal Resources ; Summary -- Chapter 2. Tort Law and Product Liability ; Negligence ; Intentional Torts ; Product Liability ; Summary -- Chapter 3. Risk Management ; Perspectives on Approaching Risk Management ; Risk Management Process ; Summary -- Chapter 4. Agency Law ; Sport Agents ; Principals of Agency Law ; Regulation of Athlete Agents ; Consolidation ; Disputes ; Summary -- Chapter 5. Contract Law ; Basics of Contract Law ; Sport Contracts ; Contract Law Issues ; Summary -- Chapter 6. Employment Law ; Employment Relationship ; Discrimination ; Sexual Harassment ; Federal Employment Laws ; Summary -- Chapter 7. Constitutional Law ; First Amendment ; Fourteenth Amendment ; Fifth Amendment ; Summary -- Chapter 8. Gender Equity ; Title IX ; Sexual Harassment ; Employment Discrimination ; Summary -- Chapter 9. Intellectual Property Law ; Trademark Law ; Copyright Law ; Right of Publicity ; Patent Law ; Ambush Marketing ; Summary -- Chapter 10. Antitrust Law ; Federal Antitrust Laws ; Application to Professional Team Sports ; Application to Individual Performer Sports ; Application to University Sports ; Summary -- Chapter 11. Labor Law.
Includes bibliographical references
Keywords: Sports -- Law and legislation -- United States